UPAYA PENGELOLAAN KOPERASI SYARIAH BAGI KESEJAHTERAAN ANGGOTANYA PADA MASJID BESAR KECAMATAN TANJUNGMEDAR - Jundu Rizal Rizalussolih; Kosasih .; Moh. Ihsan Zaelani (STAI Sebelas April Sumedang, 2024)
In short, a sharia cooperative is a cooperative that is managed based on sharia contracts. So if a cooperative has not and does not implement the concept of Islamic sharia in its activities, then the cooperative is not yet considered a Sharia Cooperative. The purpose of establishing a cooperative as a business entity is to improve the welfare of its members. The higher the welfare obtained and felt by its members, the better the assessment and quality of the management of the cooperative. Conversely, if the welfare of its members is lower, the lower the assessment and quality of the cooperative. In order to improve the welfare of its members, the cooperative management must make various practical strategic efforts as a step towards realizing the goals of the cooperative management itself. This study aims to scientifically determine the management efforts, what are the supporting and inhibiting factors, and how the welfare of its members is at the Sharia Cooperative of the Al Hidayah Grand Mosque, Tanjungmedar District. Based on the results of the study, it was found that the management efforts of the Sharia Cooperative for the welfare of its members at the Al Hidayah Grand Mosque, Tanjungmedar District provide significant benefits for its members. This is shown by evidence that the level of satisfaction and the number of members continues to grow. In addition, members also get spiritual satisfaction when they transact according to sharia in their daily business activities. The benefits felt by members for the efforts made by the Sharia Cooperative of the Al Hidayah Grand Mosque, Tanjungmedar District are in the interval of 62.5% to 100%.